ANALISIS KUALITAS UDARA PARAMETER PM2.5 DI WILAYAH KOTA SORONG BERBASIS ISPU - Syafaati, Ayu Diah (Stasiun Pemantau Atmosfer Global Bukit Kototabang, 2023)
Sorong City has an area of 1.105 km2 and is the most densely populated area in the Provinces of West Papua and Southwest Papua. As the population in Sorong City increases, human activities also increase which can contribute to increasing PM2,5 particulate concentrations. Sources of particulates in Sorong City came from anthropogenic activities such as city development projects, transportations, biomass burning, and other public activities in the area. PM2,5 that exceeds ambient air quality standards can harm human health. PM2,5 Observations were carried out at Global Atmosphere Watch Sorong Station using BAM Met-One 1020 automatic instrument. BAM-1020 automatically measures and records the level of particle concentrations in the air using Beta Ray Attenuation principle, namely the attenuation of beta particles through the collected solid matter. on fiber filters. PM2,5 solid matter collected in the fiber filter in a volume of ambient air that is drawn by the pump. In general, during September 2021 – June 2023, PM2,5 concentrations tend to increase. The results of the analysis showed that the daily average concentration of PM2,5 measured during September 2021 – June 2023 was in the range 1.21 – 18.71 ug/m3; still below the PM2,5 threshold value of 65 ug/m3 (24 hours). Based on the calculation of the PM2,5 parameter Air Pollutant Standard Index (ISPU), it is known that the ISPU value is in the range 0 – 50. Air quality conditions in Sorong area during this time were in the good category. The influence of meteorological parameters of rainfall and air temperature on PM2,5 concentrations in Sorong City has the most significant and strongest correlation, with a value of r=0.8 (air temperature) and r=-0.7 (rainfall).